ISLAMIC INTEGRATED SCIENCE LEARNING IN JUNIOR HIGH SCHOOL - Abdullah Herman; Fachri Dermawan; Fatimah Depi Susanty Harahap; Yenni Kurniawati (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
This article's goal is to present the goals of science education at the high school level that are incorporated with Islamic principles. The study identifies some of the learning objectives that are prioritized in the context of integrating science and Islam. Understanding scientific ideas within the context of Islam, developing moral and ethical principles, comprehending the connection between science and religion, and fortifying one's Islamic identity are the main objectives of education. The findings demonstrate that the integrated approach allows students to deepen their grasp of science and increase their awareness of Islam.